Strain-dependent differences in transformation frequency - A. Clements; G. A. Marzluf (Fungal Genetics Reports, 1985)
Cloning structural and regulatory genes of Neurospora and their manipulation in vitro will allow detailed molecular study of gene structure and regulation.